A Psychometric Re-Examination of the Science Teaching Efficacy and Beliefs Instrument (STEBI) in a Canadian Context - Neda Moslemi; Amin Mousavi (MDPI AG, 2019)
A teacher’s self-efficacy has been found to be one of the most important factors contributing to a successful teaching–learning outcome for both the teacher and the students. Numerous studies have shown that there is a relationship between students’ self-efficacy, students’ academic achievement, teacher burnout and a teacher’s sense of self-efficacy. In this study, the psychometric properties of the Science Teaching Efficacy and Beliefs Instrument (STEBI) by Riggs and Enochs (1990) were re-examined in a Canadian context utilizing data of 1630 teachers from the Pan-Canadian Assessment Program (PCAP) in 2013. Exploratory factor analysis (EFA) and its associated methods were used to investigate the factorial structure of the STEBI, and Cronbach’s alpha was calculated as a measure of reliability. The results showed adequacy of a two-factor solution and similar overall patterns of factor loadings across orthogonal and oblique rotations. In terms of reliability analysis, both factors had reliability coefficients lower than the original scale. The implications of these findings and the future directions for research are discussed.